Research at the Nexus Between Physical Education and Environmental Education: A Narrative Integrative Review Through a Physical Literacy Lens - Johannes Carl; Kathryn Riley; Jacqui Peters; Peta J. White (Australian Journal of Environmental Education)
Following inter-/transdisciplinary ideas, environmental education inherently collaborates with other subjects, including physical education. As the work with other subjects might be jeopardised by differing worldviews and paradigms, it is worth illuminating compatible and incompatible positions for inter-/transdisciplinary work. In physical education, the concept of physical literacy (PL) has recently gained considerable attention and adopts a student-centred perspective on human existence and learning. Therefore, the goal of the present narrative integrative review was to review the existing literature at the nexus between physical education and environmental education through a PL lens (five pre-defined concept assumptions). After screening for eligibility, a total of 129 articles were assigned to five different thematic categories: (a) conceptual discussion/argumentative patterns, (b) curricular discussion and international comparisons, (c) programming/intervention content, (d) teacher and enabler perspectives and (e) student outcomes/perspectives. The synthesis revealed that PL can harmonise with the educative work when respecting the disciplinary interests of both physical education and environmental education. However, few intervention studies translate the holistic PL claims into interventions. Accordingly, evaluations with teachers or students less frequently integrated holistic learning experiences in line with PL. In summary, previous research at the nexus has not yet exhausted its full inter-/transdisciplinary potential.